Tourism destination competitiveness in São Tomé and Príncipe - Loureiro, S. M. C.; Ferreira, E. S. (Anatolia, 2015)
São Tomé and Príncipe (STP) is a small African archipelago that has been suffering from serious ongoing social, environmental, and economic constraints that have restricted its development process in recent years. Therefore, it is crucial to find alternative ways of development that may overcome these disadvantages. On the basis of 27 interviews conducted in STP, this article reflects on tourism destination competitiveness in this archipelago. The findings reveal that the qualifying determinants are natural resources, unique landscape, cocoa and coffee plantations, and peace and safety. However, we can also find some competitive weaknesses, such as infrastructure, technical training for tourism, lack of coordination among ministries and interrelationship among organizations, and weak external marketing communication.